KUALITAS PELAYANAN ADMINISTRASI DI DESA SABAH BALAU - Apriyani, Yuyun (Jurnal Progress Administrasi Publik, 2023)
One of the main tasks that is very crucial for the government is to guarantee quality public services for citizens. Therefore, government agencies are often referred to as "public servants" or "public services". In providing services to the community, there are still many service implementing employees who do not understand how important quality service is to residents and have not been fully implemented properly. The purpose of this research is to understand how the quality of service administration is in Sabah Balau Village, Tanjung Bintang District, South Lampung Regency. This study uses qualitative research methods, where this research has a descriptive nature. The findings from this study indicate that the quality of community service at the Sabah Balau Village office from the point of view of the five dimensions that affect administrative services, there are two aspects that have not run optimally. So with that, employees further improve the quality of service and improve skills and discipline.   Keywords : Service Quality; Administration; Village.